Sleep duration and mortality in the elderly: a systematic review with meta-analysis. Issue 2 (17th February 2016) - Silva, Andressa Alves da; Mello, Renato Gorga Bandeira de; Schaan, Camila Wohlgemuth; Fuchs, Flávio D; Redline, Susan; Fuchs, Sandra C
Abstract : Objective: The purpose of our study was to evaluate the association between short and long sleep duration and all-cause and cardiovascular mortality among elderly individuals. Design: Systematic review and meta-analysis of population-based cohort studies. Setting: Articles were retrieved from international and national electronic databases. Study selection: Studies were identified in PubMed, EMBASE, LILACS (Latin American and Caribbean Health Sciences Literature), IBECS (Bibliographic Index on Health Sciences from Spain) and CAPES (PhD thesis repository) between 1980 and 2015. Studies which met all criteria were eligible: participants aged 60 years or over, assessment of sleep duration as 24 h, nighttime or daytime sleep, evaluation of all-cause or cause-specific mortality, population-based cohort studies conducted on representative samples. There was no language restriction and studies published as abstracts were excluded. Data extraction: Data were analysed using the Comprehensive Meta-Analysis software (V.3.3.070), and summary estimates (relative risk (RR), 95% CI) were calculated using a random effects model. Heterogeneity and consistency were evaluated through Cochran's Q and the I 2 statistics, respectively, and sensitivity analyses were conducted. Primary and secondary outcome measures: All-cause and cardiovascular mortality. Results: Overall, 27 cohort studies were selected, comprising >70 000 elderly individuals, and followed up from 3.4 to 35 years. In the pooled analysis, long and short sleep duration were associated with increased all-cause mortality (RR 1.33; 95% CI 1.24 to 1.43 and RR 1.07; 95% CI 1.03 to 1.11, respectively), compared with the reference category. For cardiovascular mortality, the pooled relative risks were 1.43 (95% CI 1.15 to 1.78) for long sleep, and 1.18 (95% CI 0.76 to 1.84) for short sleep. Daytime napping ≥30 min was associated with risk of all-cause mortality (RR 1.27; 95% CI 1.08 to 1.49), compared with no daytime sleep, but longer sleep duration (≥2.0 h) was not (RR 1.34; 95% CI 1.95 to 1.90). Conclusions: Among elderly individuals, long and short sleep duration are associated with increased risk for all-cause mortality. Long sleep duration is associated with cardiovascular mortality.